The objective character of virtues in Marsilio Ficino’s “Platonic theology” - Papiernik, Joanna (Hybris, 2016)
Marsilio Ficino did not write a methodical, complete treatise on ethics, but the ethical questions are discussed in most of his writings, including his opus magnum entitled Theologia Platonica. The most important sources for Ficino’s ethical considerations are Platonic and Neoplatonic texts and this is strongly reflected in Theologia; one of the aspects of this dependence regards the nature of virtues: they are seen as unchangeable, indivisible and that is why they are objective. The main purpose of the paper is to present the objective character of virtues in Platonic Theology by invoking their definition, role and status with references to Plato’s works.